2011
DOI: 10.21273/hortsci.46.5.727
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Slope and Channel Nutrient Solution Gap Number on the Yield of Tomato Crops by a Nutrient Film Technique System under a Warm Climate

Abstract: Inadequate oxygenation of the nutrient solution (NS) in recirculating hydroponic systems leads to root hypoxia in several plants as a result of low oxygen solubility, and this is most notable in warm climates. Hypoxia affects crop nutrient and water absorption and results in reduced crop yield. However, increased air supply to the NS serves as a source of oxygen for the roots. To evaluate the incorporation of oxygen into the system, we varied the slope of 14-m long containers from 2% to 4% and applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…In both experiments, mean fruit weight was reduced in NFT system. Yield increasing is attributed to better oxygenating of root environment has been reported in tomato (López-Pozos et al, 2011), in cucumber (Ehret et al, 2010), in pepper (Marfà et al, 2005;Urrestarazu and Mazuela, 2005), and in melon (Urrestarazu and Mazuela, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…In both experiments, mean fruit weight was reduced in NFT system. Yield increasing is attributed to better oxygenating of root environment has been reported in tomato (López-Pozos et al, 2011), in cucumber (Ehret et al, 2010), in pepper (Marfà et al, 2005;Urrestarazu and Mazuela, 2005), and in melon (Urrestarazu and Mazuela, 2005).…”
Section: Discussionmentioning
confidence: 89%
“…Most research on the influence of the slope angle of trays in hydroponics has been conducted on food crops, such as lettuce. Scientists found that the growth of 4.0% sloped NFT channels displayed up to 15% improved yield over the 2.0% slopped channels [36]. For Chinese cabbage (Brassica rapa chinensis), researchers suggested using a slope angle of 5.0%, which had the greatest effect on plant growth (leaf number, plant height, and root length) and overall weight [49].…”
Section: Discussionmentioning
confidence: 99%
“…In some scientific studies, plants were grown on NFTs on trays sloped at an angle of 1% [14]. López-Pozos et al [36] reported that the slope of the growing tray influenced the oxygenation of the NS at 4% slopes, resulting in higher dissolved oxygen compared with the 2% slope. Using a steeper slope of the NFT channel could significantly improve tomato productivity [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these advantages are allowing cultivation in small areas, reduction of the crop cycle and production throughout the year, achieving the best prices and reducing the consumption of water, of agricultural inputs and manual labor (Paulus, Dourado Neto, and Paulus 2012;Santos et al 2013). Moreover, this system allows climatic conditions to be controlled and nutrients with appropriate concentrations to be provided for the growth and development of plants, increasing the productivity and quality of the final product (L opez-Pozos et al 2011;Genuncio et al 2012).…”
Section: Introductionmentioning
confidence: 99%